Social Media As Source Study Generation Millennials - Aulita, Dea; Nurazizah, Fadila; Meilinda, Lulu; Nugraha, Derry (CV. Era Digital Nusantara, 2024)
One of the lifestyles of the younger generation, better known as the Millennial Generation, in using smartphones, is searching for information and buying and selling on the Internet. This of course includes accessing social media and using it as a source of learning material, which currently supports a lot of educational content. Social media can be integrated into Millennial Generation learning where the use of social media and learning must be planned as one. This research uses a quantitative descriptive approach, using indirect data collection techniques in the form of questionnaires that describe the variables studied and examine the relationships between variables. Based on the results of this research, at the effectiveness stage, social media is used by students more to dig up information on social media accounts such as YouTube and Tiktok . YouTube can be used as a learning tool to have a positive impact on students by increasing learning motivation, creativity and friendship between friends, so that social media can be used effectively as a learning tool. These two accounts are the accounts most followed by students. Based on the explanation of the findings above, it can be concluded that the first and second hypotheses are accepted, namely that there is a positive relationship between the Role of Social Media (X) and Effective Learning Resources (Y) in the millennial generation, namely students and high school students in Sukabumi.